Developments in mobile robotics - Kroff, Jared (Clanrye International, 2015)
Numerous researches are being conducted in the field of robotics and mobile robots have always formed an essential part of such researches. Mobile robotics is a growing integrative field associated with several other fields like mechanical, electronic and electrical engineering, cognitive, social and computer sciences. It is associated with computational vision, robotics and artificial intelligence because of being involved in the design of automated systems. Mobile robotics is gradually becoming a stimulating area because of the efforts of various researchers. This book covers numerous topics by integrating contributions from many researchers around the globe. It lays stress on the computational techniques of programming mobile robots. It explores different aspects of theory and practice of robotics and consists of two sections: "Visual Perception, Mapping, Robot Localization, and Obstacle Avoidance" and "Path Planning and Motion Planning". It aims to serve as a guide to students and researchers studying mobile robots.